Effect of Capital Structures on Firm Value with Sales Growth and Return on Sales as Control Variables in Consumer Goods Companies - Zaenal Abidin; Rizki Reinaldy Putra; Mahelan Prabantarikso (Bina Nusantara University, 2021)
One of the attempts taken by the management to maximize the value of the company to compete with its rivals is decision-making related to capital structure strategy. The research sought to determine the effect of Short-Term Debt (STD) on Total Assets (TA), Long-Term Debt (LTD) to Total Assets (TA), and Total Debt (TD) to Total Assets (TA) on firm value by using return on sales and revenue growth as control variables. The research was a correlation research to observe the relationship between one variable and various other variables. The sample was consumer goods companies, especially food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2018. With a purposive sampling technique, there were 15 companies out of a total of 27 companies that met the criteria. Data were obtained from the Indonesia Stock Exchange website in the form of financial reports and closing prices. Then, structural equation modeling was used to analyze the data. Based on the analysis, there are several results. First, STD to TA and LTD to TA have a negative and significant impact on firm value. Second, TB to TA has a negative but insignificant impact on firm value. Third, sales growth has a positive and negligible effect. Last, return on sales has a negative and substantial effect.